Whole genome sequencing in the palm of your hand: how to implement a MinION Galaxy-based workflow in a food safety laboratory for rapid Salmonella spp. serotyping, virulence, and antimicrobial resistance gene identification - Lamas, Alexandre; Garrido-Maestu, Alejandro; Prieto, Alberto; Cepeda, Alberto; Franco, Carlos Manuel (Frontiers in Microbiology, 2023)
Whole Genome Sequencing (WGS) implementation in food safety laboratories is a significant advance in food pathogen control, and outbreak tracking. However, the initial investment for acquiring nextgeneration sequencing platforms and the need for bioinformatic skills, represented an obstacle for the spreading of WGS. Long-reading technologies, such as the one developed by Oxford Nanopore Technologies, can be easily implemented with a minor initial investment, and with simple protocols which can be performed with basic laboratory equipment. Herein, we report a simple MinION Galaxybased workflow, with analysis parameters that allows its can be performed implementation in food safety laboratories with limited computer resources low resources, and without previous knowledge in bioinformatics, for a rapid Salmonella serotyping, virulence and antimicrobial resistance genes identification to control and characterize Salmonella spp. isolates. For that purpose, the single use Flongle flow cells, along with the MinION Mk1B for WGS, and the community-driven web-based analysis platform Galaxy for bioinformatic analysis was used. Three strains belonging to three different serotypes, monophasic S. Typhimurium, S. Grancanaria and S. Senftenberg, were sequenced. After 24h of sequencing enough coverage was achieved in order to perform de novo assembly in all three strains. After evaluating different tools, Flye de novo assemblies with one round of medaka polishing are optimal for in silico Salmonella spp serotyping with SISRT tool followed by antimicrobial and virulence gene identification with ABRicate. The implementation of the present workflow in food safety laboratories with limited computer resources allows a rapid characterization of Salmonella spp. isolatesThis is a cost-effective workflow that can be implemented by food safety labora-tories to control and characterize Salmonella spp in the food production chain.